2017
DOI: 10.1021/acschembio.6b01076
|View full text |Cite
|
Sign up to set email alerts
|

The SUV39H1 Protein Lysine Methyltransferase Methylates Chromatin Proteins Involved in Heterochromatin Formation and VDJ Recombination

Abstract: SUV39H1 is an H3K9 methyltransferase involved in the formation of heterochromatin. We investigated its substrate specificity profile and show recognition of H3 residues between K4 and G12 with highly specific readout of R8. The specificity profile of SUV39H1 is distinct from its paralog SUV39H2, indicating that they can have different additional substrates. Using the specificity profile, several novel SUV39H1 candidate substrates were identified. We observed methylation of 19 novel substrates at the peptide le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…Slight reduction in HupB methylation was observed in 6XHis‐HupB K214A mutant but was not statistically significant in contrast to the significant decrease in the level of HupB methylation observed for 6XHis‐HupB K138A mutant (Fig EV3B and C). This indicated that SUV39H1 was methylating HupB at lysine present at 138 position and within the motif similar to the one present around H3K9 in histone H3 and the defined SUV39H1 specificity profile (Kudithipudi et al , ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Slight reduction in HupB methylation was observed in 6XHis‐HupB K214A mutant but was not statistically significant in contrast to the significant decrease in the level of HupB methylation observed for 6XHis‐HupB K138A mutant (Fig EV3B and C). This indicated that SUV39H1 was methylating HupB at lysine present at 138 position and within the motif similar to the one present around H3K9 in histone H3 and the defined SUV39H1 specificity profile (Kudithipudi et al , ).…”
Section: Resultsmentioning
confidence: 93%
“…While the central part of the motif “ARK” was present in several proteins, the TK–ARK—KAP motif was present only in the M. tuberculosis HupB protein (amino acids 132–144, Figs E and EV3A). In addition, a recent study has identified the specificity profile of SUV39H1 and characterized non‐histone protein targets of SUV39H1 (Kudithipudi et al , ). The amino acid profile of M. tuberculosis HupB around K138 was also found to be similar to the SUV39H1 profile with an invariant arginine at −1 position and a lysine at −4 position (from K138; Kudithipudi et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the SUV39 family proteins, namely SUV39H1 (KMT1A), SUV39H2 (KMT1B), SETDB1 (KMT1E), SETDB2 (KMT1F), G9A (EHMT2) and G9a-like protein (GLP1), contain pre-SET (N-SET) and post-SET (C-SET) domains besides the SET domain and mediate H3K9 methylation [3][4][5][6]. SUV39H2 is primarily responsible for di-and tri-methylation of H3K9; H3K9me3 is associated with heterochromatin organization at pericentric and telomeric repeats, transcriptional repression, and epigenetic silencing of the domains in euchromatin [1,[7][8][9][10][11][12]. SUV39H2 possesses three protein isoforms and its exon 3 could affect its histone methyltransferases (HMTases) activity, stability, and sub-nuclear localization [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our workflow, the substrate specificity of SMYD2 is analyzed by methylation of peptide arrays to identify additional non‐histone targets in a systematic manner. Different studies already showed that the analysis of the specificity profiles of PKMTs is a powerful method to investigate their substrate recognition and based on this discover novel substrates . With this approach, we identified 32 novel peptide substrates of SMYD2 with validated methylation sites.…”
Section: Introductionmentioning
confidence: 99%